PERTANGGUNGJAWABAN PIDANA TERHADAP PERKAWINAN POLIGAMI TANPA PERSETUJUAN ISTRI YANG SAH (STUDI PUTUSAN MAHKAMAH AGUNG NO. 330K/PID/2012) - Zaid Alfauza Marpaung; Syafruddin Kalo; Madiasa Ablisar; Utary Maharany Barus (Universitas Sumatera Utara, 2014)
ABSTRACT Criminal Responsibility is the continuation of reproach objective of the offenses and subjective to a person eligible to be sent to jail for his actions. Criminal Rensponsibility lead to comprehension basically bear the punishment of the perpetrators of criminal acts. Elements of criminal responsibility among others unlawful act, error, delibérate, responsable abilities. Arranged in polygamous marriage law No 1 of 1974 concerning Marriage, Goverment Regulation No 9 of 1975 on The implementation of the law of Marriage and Compilation of Islamic law for the adherents of the religión of Islam. Polygamous marriages that do not meet the requirements as specified by law No 1of 1974 concerning Marriage, Goverment Regulation No 9 of 1975 in The implementation of the law of Marriage and Compilation of Islamic, one of them without the consent of the lawful wife (Study of The Supreme Court Decisión No 330K./Pid/2012) a criminal offensed. Criminal sanctions stipilated in Article 45 letter a Goverment Regulation No 9 of 1975 on The Implementation of the law of Marriage which is the crime of administration and also subject to the providions of Article 279 paragraph 1 of The Criminal Code which is a crime against civil position. This study was conducted to determine the criminal responsibility of the polygamous marriage without the consent of the legitimate wife (Study of The Supreme Court Decision No 330K/Pid/2012). Type of research is the study of normative. This study uses data collection methods legal literature. Data analysis was done qualitatively, making it easier to analyze the problems which will be discussed later , interpret and draw conclusions. Based of the result obtained can be concluded consideration of the judge to criminal liability study of The Supreme Court Decision No 330K/Pid/2012 polygamous marriage without the consent of the legitimate wife. The judge believes the defendant meets the criminal elements set forth in the provisions of Article 279 paragraph 1 of The Criminal Code and the defendant has meet the elements of criminal responsibility is unlawful act, error, delibérate, responsable abilities.